E-Posyandu to Improve Maternal and Child Health Services in Desa Aek Nagali - Merilan, Fina; Helmiah, Fauriatun; Nehe, Nurkarim (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Posyandu's role is to monitor the growth and development of children, detect diseases from an early age, and monitor the health of mothers and children in order to realize the social welfare of the community. With the internet as a medium for distributing information and services more effectively and efficiently, Posyandu can provide better information and services to the public through a website. Posyandu Aek Nagali Village does not yet have an information technology-based application that helps Cadres to record and find back the information handled by mothers and children. All records are still done manually on paper. Of course this is very vulnerable to data loss, data recording errors, difficulty finding data and unable to access data together. Recapitulation that is done manually is very prone to errors and will take up quite a lot of time. This manual recording process also complicates the reporting process to the village level. Likewise, when cadres report results to the Puskesmas, they still have to do manual recapitulation. This information is useful for knowing the child's growth, whether there are deviations or not. If there is a deviation, it is immediately known and followed up by medical personnel at Posyandu.